Kampania permanentna versus kampania, której nie było. Rzecz o wyborze prezydenta miasta Kielce - Kasińska-Metryka, Agnieszka; Olszewski, Piotr (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The purpose of the paper is to try to answer the question of the efficiency of permanent campaigns. In the context of elections to local governments, the behavior of the electorate seems to be influenced by factors that are somewhat different than in the case of presidential or parliamentary elections. Particular assets are the directly verifiable achievements of the candidates. Town mayors running for office for a second term are somewhat privileged, provided that during their office they managed to avoid making grave mistakes or behaving with negligence. The analysis concerns the elections for the office of mayor of Kielce in 2010, which were chosen due to the specific activity of the main candidate, that is the then mayor of Kielce, Wojciech Lubawski. The candidate’s limited election activity justifies the hypothesis that he did not run a permanent campaign and raises the question of how the strategy he adopted influenced the election results in Kielce.
A permanent campaign versus a campaign that never was. The elections for the mayor of Kielce